PENGARUH KOMUNIKASI ORANG TUA TERHADAP PERILAKU ANAK PADA MIN I LAMNO DESA PANTE KEUTAPANG ACEH JAYA - Baharuddin, Baharuddin (JURNAL AL-IJTIMAIYYAH, 2019)
This study entitled the influence of parental communication on children's behavior at MIN 1 Lamno, Pante Keutapang Village, Aceh Jaya. Communication in the family is an important factor in determining the good and bad of children. If parents instill a good attitude towards children, such as being honest, noble, humble, brave, grateful for Allah's blessings, carrying out amar ma'ruf nahi munkar and so forth, the child will grow in honesty, formed with noble character, courage and implement amar ma`ruf nahi munkar. Thus, if communication within the family is harmoniously interwoven, the child will feel that he is very valuable, so that he will foster good attitudes and behavior in the child. The purpose of this study is to get an overview of the communication of parents with their children in Pante Keutapang Village, Aceh Jaya, knowing the inhibiting factors of parent communication with their children in Pante Keutapang Village, Aceh Jaya and to find out how far parent communication affects their children's behavior at MIN 1 Lamno Village Pante Keutapang Aceh Jaya. This study uses a qualitative method, where the researcher thoroughly examines the facts found in the research location in accordance with the focus of the problem, by examining directly, then the results of the analysis data are presented and given discussion. To get accurate and reliable data, the data collection technique is done through observation, interviews and documentation. The results of the study show that: (1) communication between parents and their children in Pante Keutapang Village, Aceh Jaya sometimes runs well, but there are still not good, so that it can cause concern and anxiety for each parent. Because this parent communication greatly influences the attitudes and behavior of the child outside the home such as school and community environment; (2) factors that hinder the communication of parents with their children in the village of Pante Keutapang Aceh Jaya is due to the demands of work (career) and economic demands; and (3) the influence of parental communication on their children's behavior at MIN 1 Lamno Pante Keutapang Village, Aceh Jaya is a change in the attitude of the child while at school, such as being unable to respect the teacher, always fighting with friends, often saying rude and so on, this will also have an impact on his performance.Keywords: Influence, Communication, Children